2002
DOI: 10.1258/0022215021910708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-fungal nasal lavage with amphotericin B on nasal polyposis

Abstract: Recent studies have suggested that allergic fungal rhino-sinusitis could be involved in the development of nasal polyposis. The aim of this study was to evaluate the response of anti-fungal nasal lavages. Patients performed nasal lavage with 20 ml of a one per one thousand amphotericin B suspension in each nostril, twice a day, for four weeks. In addition, all patients continued their saline nasal lavage and their conventional topical corticosteroid spray. This study included 74 patients, with a mean age of 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 10 publications
(12 reference statements)
2
83
0
5
Order By: Relevance
“…The endoscopic findings were either reported as part of validated scoring scales (1,7,(16)(17)(18)(19)21,22,(25)(26)(27)(28) or nonvalidated systems (15,20,23,24,30) . Seven studies reported endoscopic improvement (15,(17)(18)(19)(22)(23)(24) , whereas the remainder of the studies reported no benefit (endoscopic) from antifungal agents. When the outcomes were taken into context of the methodology of individual studies, there appears to be no high quality evidence that supports the benefit of topical or oral antifungal agents in improving endoscopic outcomes in patients with AFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endoscopic findings were either reported as part of validated scoring scales (1,7,(16)(17)(18)(19)21,22,(25)(26)(27)(28) or nonvalidated systems (15,20,23,24,30) . Seven studies reported endoscopic improvement (15,(17)(18)(19)(22)(23)(24) , whereas the remainder of the studies reported no benefit (endoscopic) from antifungal agents. When the outcomes were taken into context of the methodology of individual studies, there appears to be no high quality evidence that supports the benefit of topical or oral antifungal agents in improving endoscopic outcomes in patients with AFS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies specified within their inclusion criteria for participants to have recently undergone FESS prior to the study (17)(18)(19)(20)25) or as part of the study (15,22,23,26,30) . However, a number of studies specifically excluded participants whom had recent FESS prior (range 3 to 12 weeks) to the medical intervention (16,21,27,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have demonstrated the therapeutic effects of Amphotericin B against fungi (19). Studies investigating the effects of Amphotericin B on improvement and treatment of CRS have shown different and even controversial results (20)(21)(22). Therefore, the present study aimed to determine the effect of topical Amphotericin B on improvement of the symptoms in patients with CRS.…”
Section: Introductionmentioning
confidence: 95%
“…Acerca del uso de irrigaciones nasales con terapia antifúngica en CEF, Riccheti y col 21 , investigaron la eficacia de lavados nasales con anfotericina B en pacientes con poliposis nasal tratada con CEF previa, usando 1 gr. de anfotericina B disuelto en 1.000 ml de agua destilada, 2 veces al día por 4 semanas.…”
Section: Actualización En El Tratamiento Con Soluciones Tópicas No Counclassified